Jammed Pickering Emulsion Gels - Jia Zhang; Yuan Zheng; Baoling Guo; Dongpeng Sun; Yao Xiao; Ze Yang; Rongrong Liu; Jingyi Chen; Baiheng Wu; Peng Zhao; Jian Ruan; David A Weitz; et al. (Advanced Science)
Abstract Emulsion gels with specific rheological properties have widespread applications in foods, cosmetics, and biomedicines. However, the constructions of water‐in‐oil emulsion gels are still challenging, due to the limited interactions available in the continuous oil phase. Here, a versatile strategy is developed to prepare a new type of emulsion gels, called Jammed Pickering emulsion gels (JPEGs). In the JPEG system, SiO2 NPs in the oil phase serve as colloidal surfactants to stabilize water‐in‐oil Pickering emulsions, while positively‐charged NH2‐PEG‐NH2 molecules in the water phase cross‐link negatively‐charged SiO2 NPs at the water/oil interface, making NP‐stabilized water droplets hard to deform and thus jamming the emulsion system to form emulsion gels. The strategy to prepare JPEGs is versatile and applicable to diverse oil phases. The designed JPEGs possess many advantages, including good biocompatibility for widespread applications, shear‐thinning rheological properties for easy processing, good stability Over a wide temperature range and Against centrifugation, good adhesion to wet tissues for tissue engineering, and well‐controlled sustained release Under intestinal conditions. The developed JPEGs are demonstrated to be a promising delivery platform and the strategy to achieve JPEGs will trigger more innovations of material design.